Analisis Rencana Pemasangan Transformator Sisipan Untuk Mengatasi Overload dan Drop Voltage pada Penyulang Selogabus PT. PLN (Persero) ULP Bojonegoro Kota - Sukamdi; Harrij Mukti K.; Muhammad Hadyan Farizan; Muhammad Rafid Faiz Firmansyah (Elposys: Jurnal Sistem Kelistrikan, 2022)
Transformers MA164 (250 kVA) and MA267 (250 kVA) have experienced overload (LoadMA164 = 102% and LoadMA267 = 111%) based on the loading standardization, namely SE DIR PT. PLN (Persero) No.0017/2014 (≤ 80%). The MA164 and MA267 transformers also have the farthest customer end voltages of 187 V (ΔVMA164 = 23%) and 189 V (ΔVMA267 = 22%) which do not comply with SPLN standard No. 1 Th. 1995 (+5% and -10%). An effective solution is to install an insert transformer because MA164 and MA267 cannot be uprated and cannot be broken by the JTR load. For planning the installation of the insert transformer it is necessary to carry out load forecasting, determination of the capacity of the insert transformer, division of the line of the farthest customer parts, determination of the location and selection of distribution substation accessories.The MA164 insert transformer (160 kVA) is installed at a distance of 416 m from the MA164 Transformer with a loading of 47%, while the MA267 insert transformer (200 kVA) is installed at a distance of 255 m from the MA164 Transformer with a loading of 47%. After installation the insert transformer MA164 transformer has a load of 77% and a end voltage of 211.9 V (ΔVMA164 = 9%), while the MA267 Transformer has a loading of 62% and an end voltage of 212.7 V (ΔVMA267 = 8%). With the appropriate conditions, the transformer can function properly and the customer's electrical equipment can function normally.